Outcomes of Surgical Management of Severe Lumbar Spinal Canal Stenosis - Ige, Oluwole O.; Lawal, Opeyemi A.; Olufemi, Temiloluwa O.; Ojodu, Ishaq B.; Igbinoba, Bright A.; Alao, S. O (Nigerian Journal of Orthopaedics and Trauma, 2019)
Background: Lumbar Spinal Canal Stenosis (LSCS), requiring surgical intervention is a common presentation in Orthopaedic practice in Nigeria. Although it is well established that surgery is very effective in relieving the symptoms of this condition, there is a paucity of reports of surgical treatment outcomes of LSCS in Nigeria. Objective: The study aims to report the early outcomes of surgical treatment of LSCS in the study centre. Methods: Prospective Observational Pretest and Post-test Study at a single centre, the University of Medical Sciences Teaching Hospital, located in Ondo State in Southwest Nigeria, West Africa. The study was done between January 2015 and June 2017. Preoperative and postoperative data collected from 32 patients with a diagnosis of LSCS who had Decompressive Laminectomy with or without instrumented fusion were analyzed for relief of symptoms: pain, functional wellbeing and general health status using Visual Analogue Scale (VAS) for back and leg pain, Oswestry Disability Index (ODI) and Short Form 36 (SF 36). Results: Excellent to good pain relief was reported by 31 (96.9%) and 30 (93.8%) of the patients for leg and back pain respectively at 6 months, 1 (3.1%) reported a fair outcome for leg pain while 2 (6.2%) reported fair outcome for back pain. No patient had a poor pain relief outcome. Functional outcome and general health status were also excellent/good for 28 (87.5%) and 29 (90.6%) respectively. There was no mortality or major cardiorespiratory event recorded. However, there was a minor complication rate of 68.8% (22 patients). These include dural tears 16 (50%), deep vein thrombosis 1 (3.1%), postoperative neurological weakness 2 (6.2%), wound infection 20 (62%), wound dehiscence 10 (31%), reoperation 6 (18.6%). The outcome at 24 weeks was unaffected by these minor complications. Conclusion: Although associated with early perioperative minor complications, Spine surgery is an effective and safe therapeutic option for the relief of LSCS symptoms with short term good clinical outcomes.